Everything is possible! - Parent, Nancy (Houghton Mifflin Harcourt, 2018)
Mary Poppins returns to 17 Cherry Tree Lane to visit the Banks family following a personal loss, and, with the help of Jack the lamplighter, brings joy and wonder back into their lives.
At head of title: Disney Mary Poppins returns.
"Screenplay by David Magee. Based on the series of books by P.L. Travers."
Keywords: Poppins, Mary -- (Fictitious character) -- Fiction; Household employees -- Fiction; Family life -- Fiction; Fantasy